Abdominal rhabdoid tumor presenting with symptomatic spinal epidural compression in a newborn. A case report - Montalto, Shana; Di Filippo, Michela; Capra, Valeria; Manzitti, Carla; Sementa, Angela Rita; De Marco, Patrizia; Ognibene, Marzia; Sertorio, Fiammetta; Sorrentino, Stefania (Frontiers in Pediatrics, 2024)
The occurrence of an abdominal tumor invading the spinal canal and causing symptoms of epidural compression is rare in an infant, and exceptional at birth. Peripheral neuroblastic tumors are by far the most common cause. Emergency chemotherapy is commonly curative, though permanent sequelae are possible. Although other malignancies may be involved, no case of rhabdoid tumors at birth has been reported. We describe the case of a neonate who presented symptoms of spinal epidural compression at birth secondary to a rhabdoid tumor. As expected with this highly malignant tumor, the patient experienced a rapidly progressive clinical course and died within three months of diagnosis.